A photovoice research: Connecting youth with the environment through visual literacy and photography - Leggett, Aislinn (The Canadian Art Teacher / Enseigner les arts au Canada)

(untitled) (Canadian Society for Education through Art / Société canadienne d’éducation par l’art, 2025)
In 2023-24 I facilitated a photovoice workshop as part of my thesis research, working with students in Grades 5 through 8 from Namur School. The workshop was a six-week extra-curricular activity held twice weekly during the students’ lunch break in the school library. The design research is a combination of Wang and Burris’ original method combined with contemporary variants to adapt the methodology to specifically fit my research, the participants and project location. The environment was the theme of the workshop, as we explored the forest behind the student’s school to engage in an eco-responsible relationship through photography and group discussions. The outcome was a group exhibit installed in the school, where the students invited the local and school community to attend their vernissage. The following discusses the participating student’s process, anecdotes from the workshop and photovoice as a methodology.